Building your first mobile game using XNA 4.0 : a fast-paced, hands-on guide to building a 3D game for the Windows Phone 7 platform using XNA 4.0 /: a fast-paced, hands-on guide to building a 3D game for the Windows Phone 7 platform using XNA 4.0. (2012) - Unknown
No abstract available